Cell Proliferation in Cutaneous Malignant Melanoma: Relationship with Neoplastic Progression. (11th January 2012) - Piérard Piérard, G. E. G. E.
Abstract : The establishment of the diagnosis of cutaneous malignant melanoma (CMM) always calls for histopathological confirmation. Further to the recognition of the CMM aspects, immunohistochemistry is helpful, in particular, in determining the size of the replicative compartment and the activity in each of the cell cycle phases (G1, S, G2, M). The involvement of cancer stem cells and transient amplifier cells in CMM genesis is beyond doubt. The proliferation activity is indicative of the neoplastic progression and is often related to the clinical growth rate of the neoplasm. It allows to distinguish high-risk CMM commonly showing a high growth rate, from those CMMs of lower malignancy associated with a more limited growth rate. The recruitment and progression of CMM cells in the cell cycle of proliferation depend on mitogen-activated protein kinase (MAPK) pathway and result from a loss of control normally involving a series of key regulatory cyclins. In addition, the apoptotic pathways potentially counteracting any excess in proliferative activity are out of the dependency of specific regulatory molecular mechanisms. Key molecular components involved in the deregulation of the growth fraction, the cell cycle phases of proliferation, and apoptosis are presently described in CMM.